A Systematic Review of Culturally Tailored Obesity Interventions among African American Adults. Issue 3 (4th May 2017) - Burton, Wanda Martin; White, Ashley N.; Knowlden, Adam P.
ABSTRACT: Background : African Americans have the highest age-adjusted rates of obesity at 48.1%. High rates of obesity contribute to the disproportionate share of chronic health conditions. In order to reduce these high rates and achieve health equity, intervention programs must address racial health disparities in culturally meaningful ways.Methods : The purpose of this investigation was to systematically review culturally tailored interventions conducted between 2005 and 2015 aimed at reducing obesity among African American adults. Several databases were used with search terms "African American adults, " obesity, " and "intervention." Inclusion and exclusion criteria were used.Results : The search returned a total of 147 hits and after the 3-phase data extraction process, 8 studies met inclusion and exclusion criteria.Discussion : The interventions focused on individual-level change and most included a primarily female sample. Faith-based settings appear to be an ideal setting. Given the small amount of studies conducted over the past decade, there is a need for more interventions that use culturally appropriate strategies.Translation to Health Education : Sociocultural and constituent-involving strategies appear to allow meaningful interaction with communities and may help with the high attrition rate. Age and gender should be a focus, in addition to race, when planning interventions.